2013
DOI: 10.1111/jerd.12054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Vertical Position of Maxillary Central Incisors on the Perception of Smile Esthetics Among Orthodontists and Laypersons

Abstract: The upper central incisors are the key determinant in evaluating smile esthetics, and thus, the assessment of their ideal vertical positioning is an aspect of paramount importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
4
29

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(146 citation statements)
references
References 26 publications
10
103
4
29
Order By: Relevance
“…In contrast, the key aspect found in this research was that minimal maxillary incisor exposure was extremely unattractive. Although a similar study evaluating the aesthetic perception at repose was not found in the literature, Machado et al [2] evaluated the perception of smile aesthetics with respect to different vertical positions of the maxillary central incisors and found that slightly extruded incisors were more attractive than slightly intruded incisors.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In contrast, the key aspect found in this research was that minimal maxillary incisor exposure was extremely unattractive. Although a similar study evaluating the aesthetic perception at repose was not found in the literature, Machado et al [2] evaluated the perception of smile aesthetics with respect to different vertical positions of the maxillary central incisors and found that slightly extruded incisors were more attractive than slightly intruded incisors.…”
Section: Discussionmentioning
confidence: 95%
“…Those examples could not only decrease the maxillary incisor exposure leading to the appearance of premature aging but also create a reverse smile arc, which is considered very unattractive [2,10,17,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations